Ophthalmologic findings in child in the Cornelia de Lange syndrome - Sielicka, Danuta; Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina; Średzińska-Kita, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Purpose: Cornelia de Lange syndrome is a rare disease showing characteristic facial appearance, development delay, low birth weight, skeletal anomaly, hirsutism and various ophthalmologic and hearing findings. Material and methods: We described ophthalmologic problems in 2 years old girl. Results: We have find arched eyebrows, long lashes, epiphora, ptosis, nystagmus, myopia, and fundus eye changes. Conclusions: We recommend early ophthalmologic examination in patients with Cornelia de Lange syndrome.